Analisis Gaya Bahasa dalam Lirik Lagu “Semua Aku dirayakan” Karya Nadin Amizah Kajian Stilstika - Nadia Maulina; Dwi Wahyu Candra Dewi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The aim of this research is to study and analyze the language styles contained in the lyrics of Nadin Amizah's song